1995
DOI: 10.1074/jbc.270.10.5469
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-terminal Domain Truncation Alters Apolipoprotein A-I in Vivo Catabolism

Abstract: Apolipoprotein A-I (apoA-I), the major protein of high density lipoproteins, facilitates reverse cholesterol transport from peripheral tissue to liver. To determine the structural motifs important for modulating the in vivo catabolism of human apoA-I (h-apoA-I), we generated carboxyl-terminal truncation mutants at residues 201 (apoA-I201), 217 (apoA-I217), and 226 (apoA-I226) by site-directed mutagenesis. ApoA-I was expressed in Escherichia coli as a fusion protein with the maltose binding protein, which was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 70 publications
3
51
1
1
Order By: Relevance
“…A number of large fragments of apolipoprotein A-I have been observed previously by 2-dimensional electrophoresis suggesting susceptibility of this protein to degradation in vivo [23]. Shortening of apolipoprotein A-I significantly affects its distribution among lipoprotein particles and circulating half-life [24]. All of the protein fragments previously observed by 2-dimensional electophoresis are substantially larger than those described here.…”
Section: Resultscontrasting
confidence: 37%
“…A number of large fragments of apolipoprotein A-I have been observed previously by 2-dimensional electrophoresis suggesting susceptibility of this protein to degradation in vivo [23]. Shortening of apolipoprotein A-I significantly affects its distribution among lipoprotein particles and circulating half-life [24]. All of the protein fragments previously observed by 2-dimensional electophoresis are substantially larger than those described here.…”
Section: Resultscontrasting
confidence: 37%
“…Alternatively, reduced phospholipid binding affinity may account for this observation as this property associates with a greater fractional catabolic rate among some apoA-I mutants (50). Injection of a 4-fold greater dose of the ⌬7-43 and ⌬7-65 apoA-I Ad5 resulted in plasma levels of these proteins similar to Wt apoA-I (Fig.…”
Section: The N Terminus Of Apoa-i Is Essential For Hdl Maturationmentioning
confidence: 98%
“…Recent studies using truncation mutants of the carboxyl-terminal region demonstrated that the domain corresponding to residues 227-243 was critical in modulating the association of apoA-I with lipoproteins as well as in the in vivo metabolism of apoA-I (40,42). Other investigations show that substitution of the carboxyl-terminal region of apoA-I with a helical domain derived from apoA-II increases its hydrophobicity but does not restore the mutant protein's lipoprotein affinity or its ability to associate with HDL 3 (42).…”
Section: Table II Reaction Kinetics Of Recombinant Hdl Particles Withmentioning
confidence: 99%
“…The carboxyl-terminal region or repeats 9 and 10 (residues 209 -243) of apoA-I has been proposed to be important in cell binding (39), lipoprotein association (40,41,42), LCAT activation (25)(26)(27), and in vivo metabolism of HDL (40,42). Recent studies using truncation mutants of the carboxyl-terminal region demonstrated that the domain corresponding to residues 227-243 was critical in modulating the association of apoA-I with lipoproteins as well as in the in vivo metabolism of apoA-I (40,42).…”
Section: Table II Reaction Kinetics Of Recombinant Hdl Particles Withmentioning
confidence: 99%